2017
DOI: 10.2215/cjn.03570417
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Long-Term Safety of C.E.R.A. Maintenance in Pediatric Hemodialysis Patients with Anemia of CKD

Abstract: Using a defined conversion factor, 4-weekly C.E.R.A. was efficacious in maintaining hemoglobin levels in pediatric patients with stable anemia of CKD undergoing hemodialysis, switching from maintenance treatment with epoetin alfa/beta or darbepoetin. Safety was consistent with the known C.E.R.A. safety profile in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…In a typical 9‐year‐old patient, with a body weight of 25 kg, representing the 6‐11 years age category, Hb 0 is expected to be 8.1 g dL −1 . This may explain why younger patients required higher doses relative to their starting dose compared to older patients to achieve the same target of Hb of 10–12 g dL −1 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a typical 9‐year‐old patient, with a body weight of 25 kg, representing the 6‐11 years age category, Hb 0 is expected to be 8.1 g dL −1 . This may explain why younger patients required higher doses relative to their starting dose compared to older patients to achieve the same target of Hb of 10–12 g dL −1 .…”
Section: Discussionmentioning
confidence: 99%
“…in the anaemia correction setting, one in patients on dialysis (PK data from 59 patients) and one in patients not on dialysis (PK data from 65 patients), and from the DOLPHIN study of IV C.E.R.A. in paediatric patients (PK data from 63 patients). Details of the studies and data used in this analysis are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations